Segmentation K-Means Clustering Model With SPSS Program Case Study Customer the Park Mall Sawangan - Mulyono, Rynto; Sekar Ndini, Ayu; Kharisma, Gilang; Heikal, Jerry (Syntax Literate, 2023)
In a transitioning word, specially in mall property industry, a winning strategy comes from anticipating with people needs and desires, understanding them in the most holistic way possible. The 7P marketing mix refined by Booms and Bitner in 1981 which consists of elements of Product, Price, Place, Promotion, People, Physical evidence, Processes and additional Partnerships, is a tool for analyzing existing market conditions in more depth. In addition, to meet customer wants, needs, and satisfaction refers to the market environment, both external and internal. This research succeeded in modeling customer segmentation based on clustering data mining techniques with K-Means analysis using the SPSS program. Based on the analysis results obtained, there are 3 clusters, namely clusters: consumptive customer, potential customer, and standard young customer. From the results of this study, we get the personas that emerge as a result of this clustering analysis, and identify the needs, desires, and preferences of the cluster that is formed. We choose to develop tactic 8Ps marketing mix for cluster potential customer.